Tata Kelola Layanan Pajak Bumi Dan Bangunan (PBB) Online Di Badan Pendapatan Daerah (Bapenda) Kota Tangerang - Maulana, Muhammad Hafiz; Asmawi, M Rosul; Rantau, Muhammad Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2024)
Land and Building Tax (PBB) is a form of tax that is imposed based on the type of object being taxed. The objects on which PBB is based include land and buildings. This means that in the PBB imposition process, the focus is given to the land and buildings themselves, without considering the situation or identity of the subject or individual being taxed. One form of innovation that has been implemented in the provision of tax payment services, especially land and building tax, is through the PBB online payment system via the Tangerang Live platform. This innovation is regulated in Regional Regulations (Perda) relating to the Land and Building Tax Payment process. The Tangerang City Government, through the Tangerang City Regional Revenue Agency, continuously strives to provide convenience in services to taxpayers who have the obligation to pay taxes on land and buildings in the Tangerang City area. This step was realized with the launch of the Rural and Urban Land and Building Tax (PBB-P2) online service in 2018. Through this online PBB-P2 service system, taxpayers are given the convenience of submitting requests for PBB-P2 related services without being limited by location. and time. This service can be accessed easily via the official PBB-P2 Tangerang City service website at pbb.tangerangkota.go.id. The approach taken in this research is qualitative, using data collection methods through in-depth interviews. The aim of this research is to analyze the Governance of online Land and Building Tax Services at the Tangerang City Regional Revenue Agency. In this research, the principles of good governance, as defined by UNDP in Mas'ud (2012), namely transparency, participation and accountability, are used as a guide in assessing and understanding the management of online PBB services in the Tangerang City Bapenda. The management of Online Land and Building Tax (PBB) services at the Tangerang City Bapenda provides convenience and efficiency in the tax administration process for taxpayers. With this service, people can make payments, view information and manage tax data online, reducing dependence on manual processes. The Tangerang City Regional Revenue Agency (Bapenda) has taken a strong commitment to continue to improve and perfect online PBB services. The aim is that this service can provide optimal benefits for the community and at the same time also strengthen regional income.